Management Improving Seventh Grade Students’ Short Story Reading Skills Through Inquiry Based Learning: Classroom Action Research at SMP Negeri Satap 3 Gunung Bintang Awai - Ayesno; Esti Swatika Sari (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This classroom action research examined the use of inquiry-based learning to improve the short-story reading skills of seventh-grade students at SMP Negeri Satap 3 Gunung Bintang Awai. The study involved seven students and was conducted in two cycles, each comprising planning, action, observation, and reflection. Data were collected through short-story reading tests, classroom observation, and documentation. For consistency, short-story reading skill was treated primarily as the ability to understand a story and analyze its intrinsic elements, while oral reading behaviors were used as supporting process observations. The action was considered successful when at least 80% of the students achieved the minimum mastery criterion of 70 and classroom activity reached the predetermined criterion. The mean score increased from 64.29 in the pre-cycle to 69.86 in Cycle I and 80.29 in Cycle II. The mastery percentage rose from 28.57% to 42.85% and then to 100%, while the minimum and maximum scores in Cycle II were 70 and 86. Classroom observations also indicated improved participation, confidence, attention, and engagement after the instructional adjustments made in Cycle II. These findings show that inquiry-based learning supported progressive improvement in both the learning process and reading achievement within this classroom context.